2010
DOI: 10.1002/zoo.20235
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of rank and ovarian activity on the social behavior of captive female African elephants

Abstract: Over a third of captive female African elephants in North America fail to exhibit normal estrous cycles based on long‐term serum progestagen analyses. Why acyclicity occurs is unknown; however, the majority of noncycling females are ranked by keepers as the dominant individual within the group. To investigate the relationship between ovarian cyclicity status and keeper‐determined social rank, observations were conducted on 33 female African elephants (18 cycling, 15 noncycling). Based on keeper evaluations, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It was originally believed that elephant females were either cyclic or acyclic [Brown, 2000], but now many Asian and African cows have been shown to alter between periods of normal cyclicity and irregular or acyclicity during the prime reproductive years (11–35 years of age). Research over the past 10 years have investigated possible causative factors for abnormal cyclicity, such as seasonality [Bechert et al, 1999], herd rank and time spent outdoors [Schulte et al, 2000], and behavioral influences of herd mates [Freeman et al, 2004, 2009, 2010]. Wild elephants are generally not considered seasonal breeders, although fluctuations in estrus activity can occur during times of climate change, i.e., drought and monsoon seasons [Douglas‐Hamilton, 1975; Moss, 1983].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally believed that elephant females were either cyclic or acyclic [Brown, 2000], but now many Asian and African cows have been shown to alter between periods of normal cyclicity and irregular or acyclicity during the prime reproductive years (11–35 years of age). Research over the past 10 years have investigated possible causative factors for abnormal cyclicity, such as seasonality [Bechert et al, 1999], herd rank and time spent outdoors [Schulte et al, 2000], and behavioral influences of herd mates [Freeman et al, 2004, 2009, 2010]. Wild elephants are generally not considered seasonal breeders, although fluctuations in estrus activity can occur during times of climate change, i.e., drought and monsoon seasons [Douglas‐Hamilton, 1975; Moss, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that captive females who hold dominant herd status are more prone to be acyclic [Freeman et al, 2004, 2010]. But according to the 2008 survey data, the majority of acyclic Asian and African elephants were ranked in the middle category.…”
Section: Discussionmentioning
confidence: 99%
“…Although resources are typically abundant, competition can still occur between elephants in captivity [Freeman et al, 2010] and in the wild [Archie et al, 2006]. In this study, there was only one pile of hay available during control sound and experimental sound trials.…”
Section: Discussionmentioning
confidence: 91%
“…As has been discovered for a host of wildlife species, the challenge with such studies is that social hierarchy is not simply a reflection of bouts of overt aggression, but rather a culmination of subtle or affiliative interactions among group mates (Sapolsky 1990;Virgin and Sapolsky 1997;Burks et al 2004;Creel 2005;Freeman et al 2010). This probably has been best studied in species like the African elephant (Loxodonta africana) where higher social rank is expressed by one individual approaching herd-mates and initiating a behavioural interaction (Freeman et al 2010). The outcome of such an interface can then be related to reproductive success.…”
Section: Introductionmentioning
confidence: 99%